Implementation of the first Objective Structured Practical Examination in veterinary medicine in Spain: a two-year experimental study - Carrasco, Lara; González, Gema; Utrilla, Maria; Rico-San Román, Laura; Magro, Antonio; Pérez-Villalobos, Natividad; Martín-Maldonado, Bárbara (Frontiers in Veterinary Science, 2025)
BackgroundIn Veterinary Medicine, traditional methods for evaluating technical skills, such as multiple-choice exams or short questions, have limitations in assessing practical competencies. The Objective Structured Clinical Practical Examination (OSPE) has been successfully implemented in other Health Sciences degrees to improve objectivity and minimize bias in skill evaluation. This study aimed to assess the outcomes of implementing OSPE for evaluating Veterinary students' technical skills and to analyze students' perceptions and satisfaction with the method.MethodsOver two academic years, OSPE was introduced as an evaluation tool for Veterinary students, featuring four stations: Clinical Examination, Blood Sample Extraction, Anesthesia, and Surgery. Student performance was recorded, and their perceptions were gathered through voluntary surveys. Descriptive statistics were applied to analyze the exam results and survey responses.ResultsA total of 144 students participated, with 93.8% passing the OSPE on their first attempt. Among the stations, the Surgery station received the highest scores both in student performance and survey feedback. Overall, 96% of students considered OSPE a positive evaluation method, and 92.7% acknowledged its effectiveness in assessing practical skills.ConclusionsThe OSPE has significantly improved the evaluation of practical skills in Veterinary Medicine, offering an objective and structured approach that enhances learning strategies. Students demonstrated high satisfaction with the method, which also resulted in favorable exam outcomes.